Investigation on Fish Marketing Pattern in Mymensingh - Goon, PK; Chandra, KJ; Sultana, N (Journal of Environmental Science and Natural Resources, 2012)
An investigation was carried out on fish marketing system of Mymensingh town to find out different marketing channels, fish trading, marketing cost and margins of fish at different levels. The investigation was conducted from October, 2010 to September, 2011 in sixteen markets of Mymensingh town. In Mymensingh town a large number of people were involved in the fish marketing channel as bepari, aratdar, paiker and retailer. Paiker and bepari bought fish from producer and finally sold fish to retailer through aratdar. In the study area it was estimated that total marketing cost of fish for aratdar was Tk. 1.32, paiker, Tk. 6.05, and retailer, Tk. 1.83 per kg of fish. Cost item of fish for different intermediaries was Tk. 10.49 total. The highest marketing costs (Tk. 6.05) were for paiker because they had paid higher aratdari commission and higher transportation cost. Average Net profit was Tk. 3.19 for paikers at peak period and Tk. 3.36 at lean period, for aratdars Tk. 1.60 at peak period and Tk. 1.75 lean period and for retailers Tk. 5.06 at peak period and Tk. 6.24 at lean period per kg of fish. Ilish (Tenualosa ilisha) had high demand to consumers and available in the market with approximate price of Tk. 250 to Tk. 300 per piece DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11554 J. Environ. Sci. & Natural Resources, 5(1): 61-68, 2012